(untitled) (International Seven Journal of Health Research, 2023)
This review addresses the fundamental role of smell in human life, including its function in detecting odors, influencing personal preferences, and social behaviors. The article discusses the anatomy of the olfactory system, covering the structures involved in olfactory detection and processing. The evaluation of olfactory function is explored using different approaches, such as standardized tests, clinical examinations, and imaging techniques, which allow an accurate assessment of olfactory capacity and assist in the diagnosis of olfactory-related disorders. Additionally, conditions such as anosmia and dysosmia are addressed, investigating their causes, impacts, and diagnostic methods. Anosmia may be due to lesions in the olfactory structures or underlying medical conditions, while dysosmias involve qualitative alterations in the perception of smell. The article also discusses the prevalence of olfactory alterations in different contexts, including the COVID-19 pandemic, which has shown association with temporary or persistent loss of smell. Finally, the importance of advancing research in this area for a thorough understanding of the pathophysiology of olfactory alterations is emphasized. This understanding is critical for the development of personalized and effective therapeutic strategies. Collaboration between researchers and healthcare professionals is essential to drive scientific and clinical advances related to this topic. It is hoped that this review will provide a comprehensive overview of olfaction, contributing to a better understanding of olfactory mechanisms and supporting more effective clinical approaches to the diagnosis and treatment of olfactory disorders. DOI:https://doi.org/10.56238/isevjhv2n2-013